The ecological nature of the classroom environment for the perceptual learning of Additional Language speech: A natureza ecológica do ambiente da sala de aula de língua adicional para a aprendizagem perceptual da fala - Reis, Felipe Santos dos; Kickhöfel Alves, Ubiratã (Revista do GEL, 2024)
The aim of this paper is twofold: first, to discuss the notion of “environment” from the perspective of Ecological Psychology, and second, to identify potential affordances that learners may perceive in the additional language classroom, given their relations with social events and objects therein. Considering its importance in the field of speech perception, we set out to review the philosophical underpinnings of the Perceptual Assimilation Model (PAM) and its extension to Second Language Speech Learning (PAM-L2), proposed by Best (1995) and Best and Tyler (2007) respectively, especially regarding the distinction between learning additional languages “in natural communicative contexts vs. in more constrained contexts […] where the target language is not widely used” (Best; Tyler, 2007, p. 19). According to the authors, the additional language classroom in non-native communities is considered “[…] a fairly impoverished context for L2 learning” (Best; Tyler, 2007, p. 19), highly dependent on non-native teachers’ “variable” or even “incorrect” pronunciation. However, we argue that additional language classrooms can promote the emergence of new action systems in learners so that new information in relatively unfamiliar speech can be picked up, and new affordances can thereby be perceived and acted upon (Gibson, E. J.; Pick, 2000).